24-hour levodopa-carbidopa intestinal gel may reduce troublesome dyskinesia in advanced Parkinson's disease. (December 2018) - Cruse, Belinda; Morales-Briceño, Hugo; Chang, Florence; Mahant, Neil; Ha, Ainhi; Kim, Samuel; Wolfe, Nigel; Kwan, Vu; Tsui, David; Griffith, Jane; Galea, Donna; Fung, Victor
Abstract Levodopa-carbidopa intestinal gel (LCIG) is effective for the control of motor fluctuations in Parkinson's disease (PD). The objective of this study is to report the reduction of dyskinesias after transitioning from 16 to 24-h/day LCIG infusion. From a cohort of 74 PD patients treated with LCIG for motor fluctuations, we identified 12 patients that were treated with 24-h per day infusion with the aim to control troublesome daytime dyskinesia. Clinical, demographic, dyskinesia rating scales were evaluated. Daytime dyskinesia was reduced in 75% (9/12) patients following treatment with 24-h therapy, including 7 who were compared with 16-h therapy and 2 that were transitioned from oral dopaminergic therapy to 24-h LCIG. Combining the data from all 12 subjects, troublesome dyskinesias were reduced during 24-h LCIG; UPDRS 4.1 (time spent with dyskinesias) mean change was −1.5 ± 0.75, p  = 0.010 (Wilcoxon signed-rank test) and UPDRS 4.2 (functional impact of dyskinesias) mean change was −1.7 ± 0.90, p  = 0.016, without changing their UPDRS part 3 "ON" scores (p  = 0.138) or H&Y (p  = 0.157). In 5 patients, improvement in dyskinesia occurred despite an overall increase in the total daily levodopa dose. None of the patients had worsening of dyskinesia after a median follow-up of 28 months. 24-h per day infusion of LCIG may be a useful strategy in the management of troublesome dyskinesias in PD patients with disabling dyskinesias resistant to attempts to optimise 16-hours per day therapy. We postulate that this may be due to a pharmacodynamic as opposed to pharmacokinetic mechanism. Motor symptoms: the benefits of round-the-clock drug delivery Continuous 24-h intestinal administration of Parkinson's disease (PD) drugs in a gel formulation helps control disabling dyskinesias in patients with advanced PD. Typically, patients treated with levodopa-carbidopa intestinal gel (LCIG) receive a continuous dose that is administered over 16 h. This regimen has been shown to efficiently and safely improve patients' motor symptoms, although in some cases, daytime dyskinesias persist. Victor Fung at the University of Sydney, Australia, and colleagues examined whether 24-h LCIG infusion offers additional benefits for the treatment of dyskinesias. They found a significant decrease in the frequency and severity of daytime dyskinesia in nine out of twelve (75%) patients, and none of them experienced a worsening of dyskinesia. These results suggest that round-the-clock LCIG is a promising approach for treating troublesome dyskinesias that are resistant to 16-h therapy.